The importance of reflection and evaluation processes in daily training sessions for progression toward elite level swimming performance. (July 2022) - Post, Aylin K.; Koning, Ruud H.; Visscher, Chris; Elferink-Gemser, Marije T.
Abstract: Self-regulated learning (SRL) involves self-directed metacognitive subprocesses and motivational beliefs that facilitate more effective and efficient learning. We investigated whether youth swimmers who are on track to becoming elite swimmers apply SRL subprocesses more frequently in their daily training sessions compared with swimmers who are not on this track. Insights into swimmers' use of training-centered SRL could advance understanding about underlying individual characteristics that contribute to optimal engagement in daily training and, consequently, progression toward elite level swimming performance. We collected data on training-centered SRL subprocesses (evaluation, planning, reflection, speaking up, effort and self-efficacy) and performance data for 157 youth swimmers aged 12–21 years (73 males and 84 females). The results of a multivariate analysis of covariance revealed significantly higher scores for reflection processes during training for high-performing swimmers but lower scores for effort compared with lower-performing swimmers (p < 0.05). A closer examination of the high-performing group showed that those demonstrating greater improvement during a season scored significantly higher for evaluation processes after training compared with those evidencing less improvement during a season (p < 0.05). Significant between-group differences in SRL subprocesses remained after adjusting for differences in weekly training hours. Youth swimmers on track to becoming elite swimmers are characterized by more frequent use of reflection processes during training and evaluation processes after training, which suggests that these swimmers' learning and training processes are more effective and efficient. Ultimately, this could contribute to a higher quality of daily training, which may result in greater improvements during a season, higher performance levels, and a greater chance of reaching the level of elite swimming performance. Highlights: Training-centered SRL is related to performance level and progression. Reflection and evaluation are key to progression toward elite level swimming performance. Effective and efficient learning extend beyond the training time spent in the pool.